Peran Serta Pemerintah Desa Dalam Upaya Pengentasan Kasus Stunting Di Desa Situsari Kecamatan Cisurupan Garut - Nurjani, Yan Yan; Sritanti, Dewi (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
The lack of public knowledge about stunting turned out to be the main reason why parents are reluctant to take their children to posyandu. This is evident from the results of interviews with mothers who have children under five, most of whom are afraid if their child is diagnosed with stunting because it is considered a disgrace. In addition, often parents do not accept that their child is considered stunted and give various reasons so that the child does not get treatment and check his growth.The purpose of this research is reflected in the formulation of the problem, namely: How is the case of stunting in Situsari Village, what is the role of the Situsari Village Government in alleviating stunting, how is the significance of the number of stunted babies in Situsari Village.This research is a descriptive research with data collection techniques through observation, interviews and documentation studies as well as content analysis techniques through data reduction, data presentation, and conclusion. From the results of the study, it was found that the participation of the Village Government in efforts to alleviate stunting in Situsari Village has been carried out well, the benefits carried out by the Village Government in stunting alleviation are felt by parents, especially in terms of food assistance and classes for mothers under five special stunting. Keywords: The Role of Village Government, Alleviation, Stunting